Use of Instagram @Buna.Indoneia Social Media in Promoting Buna Indonesia Coffee Shop to Customers - Saputra, Ikhsan; Ramli , Ruslan (Manunggal Halim Jaya, 2026)
This study aims to determine the use of Instagram social media @buna.indonesia in promoting Buna Indonesia coffee shops to customers and to determine the obstacles faced by the use of Instagram social media @buna.indonesia in promoting Buna Indonesia coffee shops to customers. In obtaining the data needed for this study, the researcher used a qualitative method, a descriptive research type with a case study approach. The results of this study indicate that the AISAS Theory specifically plays an important role in explaining how @buna.indonesia managed to attract the attention of the audience through interesting and interactive visual content. The researcher also found obstacles to using Instagram social media, namely That Unexpected changes in the Instagram algorithm often reduce the reach and visibility of content, as well as limited features, resources, including time, energy, and budget. The increasingly tight competition in the coffee industry also adds to the complexity of the challenges faced.